Integration of Strategy Human Resource Management (SHRM) and Competitive Advantage as a Human Capital Mediator in the Performance of Private Universities - Cahyani, Eni; Agusria, Lesi (International Journal of Business, Management and Economics, 2023)
Objective - to analyze the development of SHRM Integration capabilities and competitive advantages as a mediator of human capital on organizational performance, taking into account the role of human capital as a source of knowledge to be managed in order to become a competitive advantage for company performance. Design/methodology/approach –researchers designed empirical studies from a sample of 61 Private Universities (PTS) in South Sumatra Province, asking the dean or head of the study program, to assess human capital, SHRM integration, competitive advantages to improve their pts performance. Analysis techniques using SEM SmartPLS. The results of human capital research on organizational performance are not supported, the SHRM Integration variable does not mediate human capital against competitive advantage and organizational performance, but competitive advantage mediates human capital against performance as well as exogenous variables. Research limitations/implications is the data collected did not meet the expected respondent data. Theoretical and practical implications – theoretically the development of the theory of the integration of SHRM with competitive advantages to the performance of non-profit organizations. Then in practice organizations can increase their commitment to human capital management through the integration of SHRM to form a competitive advantage and ultimately improve organizational performance. Originality/value – The authors examine the impact of intellectual capital dimensions, especially human capital, on the performance of non-profit organizations, namely Private Universities in developing country clusters with the integration of SHRM and competitive advantages to show the relationship between human capital after being mediated by the scheme.